Tolbutamide induces conformational change and promotes albumin glycation - Bansode, Sneha B.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Jana, Asis K.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2015)
Tolbutamide is a first generation sulfonylurea drug used for the treatment of type II diabetes. In the present study, the effect of tolbutamide on albumin conformation was investigated using BSA as a model protein. The binding of tolbutamide induced a conformational change in albumin, which was confirmed by thioflavin T assay, ANS assay, and CD spectroscopy. Computer simulations suggested that the binding of tolbutamide increases the solvent accessibility of lysine residues, the hotspots of glycation. Furthermore, the change in conformation of albumin facilitates increased glycation, which was observed by AGE specific fluorescence and the results were corroborated by mass spectrometric analysis. This study suggested that tolbutamide enhances albumin glycation by inducing conformational change in BSA and hence could be a potential risk factor if used for a prolonged period.

Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry